The effect of equine bone marrow‐derived mesenchymal stem cells on the expression of apoptotic genes in neutrophils. Issue 3 (20th January 2021) - Salami, Fatemeh; Ghodrati, Mitra; Parham, Abbas; Mehrzad, Jalil
Abstract: Background: Bone marrow mesenchymal stem cells (BM‐MSCs), as multipotent cells with self‐renewal and plastic‐adherent properties, have immunomodulatory effects on immune cells, including neutrophils. These cells are in close proximity in bone marrow (BM) sinusoids with non‐multiplicative immature neutrophils. BM‐MSCs exert their immunomodulatory effects on adjacent cells both directly (cell‐to‐cell contact) and indirectly (secretion of soluble factors). Objectives: The aim of this study was to evaluate the effect of equine bone marrow mesenchymal stem cells (BM‐MSCs) on the expression of some pro‐ and anti‐apoptotic genes (p53, survivin and Bcl2 ) in neutrophils co‐cultured with BM‐MSCs. Methods: For this purpose, peripheral blood neutrophils were isolated and separately co‐cultured for 12 hr with both BM‐MSCs and the BM‐MSCs΄ supernatant. Four groups were included: neutrophils with only culture media (as control), neutrophils co‐cultured with BM‐MScs, neutrophils cultured with BM‐MSCs' supernatant and neutrophils cultured with lipopolysaccharide (LPS, as positive control). Then, the expression of mentioned genes (p53, survivin and Bcl2 ) was evaluated by quantitative polymerase chain reaction (qPCR). Results: Compared with control neutrophils, in neutrophils co‐cultured with both BM‐MSCs and BM‐MSCs' supernatant, the mRNA expression levels of p53, as pro‐apoptotic gene, and survivin and Bcl2, as anti‐apoptotic genes, were remarkably increased and decreased ( p  < .05), respectively. Conclusions: These data revealed the notion that the direct contact of BM‐MSCs is not obligatory for their effects on the apoptotic status of neutrophils and they affect neutrophils via soluble secreted factors, which is promising for clinical implications in equine medicine. Abstract : The aim of this study was to evaluate the effect of equine bone marrow mesenchymal stem cells (BM‐MSCs) on the expression of some pro‐ and anti‐apoptotic genes (p53, survivin and Bcl2) in neutrophils co‐cultured with BM‐MSCs. Results showed that BM‐MSCs or their supernatant decrease the mRNA expression of p53 (apoptotic gene) and increase the expression of survivin and Bcl2 (anti‐apoptotic genes). Our data revealed that the direct contact of BM‐MSCs or paracrine secretions support neutrophils against apoptosis, which is promising for their clinical applications in equine medicine.